Introduction to fluid mechanics - Nakayama, Y (Yasuki), 1916-
Fluid mechanics is often seen as the most difficult core subject encountered by engineering students. The problem stems from the necessity to visualise complex flow patterns and fluid behaviour modelled by high level mathematics. This text overcomes this difficulty by introducing the concepts through everyday examples, before moving on to the more involved mathematics. The various theories of flow have been correlated with real phenomena and, combined with numerous figures and photographs, help the reader place the subject in context. Examples from a broad range of engineering disciplines are included making this textbook suitable for all engineers studying fluid systems as part of their degree. 'Introduction to Fluid Mechanics' is translated from the best-selling Japanese book by Professor Yasuki Nakayama, and adapted for the international market by Professor Robert Boucher. Introduces the concepts through everyday examples before moving on to the more invoved mathematics. Various theories of flow are applied to real phenomena and illustrated with numerous figures and photographs Includes examples from a bread range of engineering disciplines.